Educational Impact of Notebook Covers on the Knowledge of Sixth-Grade Primary Pupils About Tooth Avulsion and Replantation: A Randomized Trial - Sedlaceck, Paulo [UNESP]; Poi, Wilson Roberto [UNESP]; Amaral, Marina Fuzette [UNESP]; Castilho, Lithiene Ribeiro; Barioni, Sônia Regina Panzarini [UNESP]; Saito, Celia Tomiko Matida Hamata [UNESP]; Brandini, Daniela Atili [UNESP] (Sage Publications Inc, 2021)
Background Tooth avulsion is a common cause of tooth loss. However, there is a significant lack of knowledge about dental trauma and the appropriate emergency procedures to handle these cases. Aim The aim of this study was to evaluate the educational effect of notebook covers illustrated with figures and informative texts about tooth avulsion and replantation in sixth-grade primary school pupils. Material and Methods Sixth-grade pupils of two public school participated in this study. An experimental group consisting of 134 pupils received notebook covers illustrated with figures and informative texts about tooth avulsion and replantation, while a control group of 108 pupils received notebooks with neutral covers. An assessment of the educational effects on pupils was performed after 9 months, with a standardized questionnaire normally used to evaluate dental trauma. Statistical analysis was conducted with SPSS 21.0 (alpha = .05) for group description and comparison using chi-square and Student t tests. Results Compared with the control group, the experimental group showed statistically significant improvements in correct meaning of dental trauma (38% vs. 58.2%); procedures to follow in the case of dental avulsion (2.8% vs. 70.9%); storing the avulsed tooth in milk (18.5% vs. 76.9%); general knowledge about dental anatomy (61.1% vs. 95.5%); and the ideal time for the tooth to remain outside the mouth prior to replantation (20.4% vs. 59.7%). Conclusion The use of notebook covers illustrated with figures and informative texts about dental trauma led to a significant increase in the knowledge of schoolchildren about tooth avulsion, first aid, and replantation.
Keywords: education; tooth avulsion; tooth replantation